Propriétés biologiques d’Helix aspersa muller. - BENAHMED, IMANE (My University, 2023)
The objective of the present study is to explore the antimicrobial, antioxidant, and anti-inflammatory properties of the mucus of the snail Helix aspersa muller from the region of Mostaganem, Algeria.The antimicrobial activity was tested against 07 pathogenic microorganisms: Bacillus cereus ATCC 10876, Bacillus subtilis ATCC 6633, Candida albicans ATCC 10231, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Staphylococcus aureus ATCC 33862, and Salmonella typhi ATCC 6539 The antibacterial activity results revealed the following diameters in descending order, with Candida albicans ATCC 10231 (09 ± 00.00 mm), Bacillus subtilis ATCC 6633, Staphylococcus aureus ATC 33862, Salmonella typhi ATCC 6539 (08 ± 00.00 mm).No antimicrobial activity was noted against strains Bacillus cereus ATCC 10876, Pseudomonas aeruginosa ATCC 27853, and Escherichia coli ATCC 25922. Antioxidant activity results confirm that mucus from the snail Helix aspersa muller has a pronounced antioxidant activity with an IC50 = 431 μg/ml and a percentage inhibition of DPPH of 57.5%. In addition, anti-inflammatory activity results show that Helix aspersa muller snail mucus is able to control autoantigen production through inhibition of protein denaturation. The denaturation inhibitory activity of BSA can be attributed to the presence of different bioactive compounds found in mucus. These results suggest the possibility of using Helix aspersa muller snail mucus as a treatment for certain infections of bacterial origin or even certain fungal infections, anti-inflammatory and even antioxidant treatment.
Keywords: Mucus; Helix aspersa muller; antibacterial activity; anti-inflammatory activity; antioxidant activity